Outcomes among patients with cancer and incidental or symptomatic venous thromboembolism: A systematic review and meta‐analysis. (12th July 2021) - Caiano, Lucia; Carrier, Marc; Marshall, Andrea; Young, Annie M.; Ageno, Walter; Delluc, Aurélien; Wang, Tzu‐Fei
Summary: Background: Patients with cancer have an increased risk of venous thromboembolism (VTE) and it is commonly detected incidentally. The outcomes and optimal management for patients with cancer and incidental VTE remain debated. Objectives: We conducted a systematic review and meta‐analysis to evaluate the outcomes in patients with cancer and incidentally detected VTE compared to those with symptomatic events. Patients/Methods: We searched the electronic databases and included randomized controlled trials (RCTs) and observational studies reporting recurrent VTE, major bleeding events, and mortality in patients with cancer and incidental VTE compared to symptomatic VTE. Results: We included 23 studies for the systematic review: 3 RCTs and 20 observational studies. The meta‐analysis of the 3 RCTs showed a significantly lower rate of VTE recurrence at 6 months in patients with incidental VTE compared to those with symptomatic VTE (relative risk [RR] 0.62, 95% confidence interval [CI] 0.44–0.87). The risk of major bleeding events at 6 months was numerically higher with incidental VTE compared to symptomatic VTE (RR 1.47, 95% CI 0.99–2.20). There was no difference in overall mortality. Conclusions: Among patients with cancer, incidental VTE was associated with a lower rate of VTE recurrence compared to symptomatic VTE, with a trend in increased major bleeding events. The risk‐benefit ratio of anticoagulation may differ between incidental and symptomatic events and should be considered in patient management.